The ABC of fabulous princesses - Puchner, Willy 1952- (NorthSouth, 2014)
"Meet the princesses from A to Z. Some are ambitious, some bashful, some dangerous ... but each of the twenty-six feathered empresses possess a uniquely charming character and come bearing an extraordinary gift for Prince William"--Publisher
Keywords: Deutsch; Suche; Alphabet; Ehefrau; Prinz; Prinzessin; Verschiedenheit; Princesses / Juvenile fiction; German language / Alphabet / Juvenile fiction; Alphabet books / Juvenile fiction; Alphabet books; German language / Alphabet; Princesses; Fiction; Juvenile works; Juvenile books; Bilderbuch